1975
DOI: 10.1172/jci108053
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of thyroxine and triiodothyronine distribution and of the conversion rate of thyroxine to triiodothyronine in man.

Abstract: A B S T R A C T Studies on peripheral metabolism of simultaneously administered 125I-labeled L-thyroxine (['I1]T4) and "1'I-labeled L-triiodothyronine ([.1.I]T3) were performed in five normal subjects, in four patients with untreated hypothyroidism, and in 3 hypothyroid patients made euthyroid by the administration of T4. The fractional turnover rate (Xos) of thyroid hormones irreversibly leaving the site of degradation and the volumes of pool 1 (serum, Vi), of pool 2 (interstitial fluid, V2), and of pool 3 (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
37
0
1

Year Published

1976
1976
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(44 citation statements)
references
References 40 publications
6
37
0
1
Order By: Relevance
“…It has been suggested that adequate replacement therapy with L-T4 would require doses sufficient to establish values for a serum T4 concentration above the normol range (Sturnick and Lesses, 1961;Lavietes and Epstein, 1964). Moreover, the amount of T3 generated by the conversion of T4 to T3 was found to contribute to approximately 70% of the daily T3 production in normal subjects and, therefore, the 30% of the T3 production was assumed to be secreted directly from the thyroid (Inada et al, 1975). In the present paper, the elevated TSH levels found in 3 patients after T4 administration were reduced to the normal range within 4 weeks after T4 and T3 administration.…”
Section: Discussionsupporting
confidence: 47%
“…It has been suggested that adequate replacement therapy with L-T4 would require doses sufficient to establish values for a serum T4 concentration above the normol range (Sturnick and Lesses, 1961;Lavietes and Epstein, 1964). Moreover, the amount of T3 generated by the conversion of T4 to T3 was found to contribute to approximately 70% of the daily T3 production in normal subjects and, therefore, the 30% of the T3 production was assumed to be secreted directly from the thyroid (Inada et al, 1975). In the present paper, the elevated TSH levels found in 3 patients after T4 administration were reduced to the normal range within 4 weeks after T4 and T3 administration.…”
Section: Discussionsupporting
confidence: 47%
“…Another correlation between the predictions of these experiments and in vivo data with respect to the effective thyroid status comes from early work by Inada et al (22). These studies showed that in hypothyroid patients, the fractional whole body conversion rate of T 4 to T 3 was 42%, while in the same patients made euthyroid with levothyroxine, this rate fell to 21%.…”
Section: Tablementioning
confidence: 77%
“…of 1.21 ± 0.24 1/day and a 98% confidence limit (mean ± 2 S.D.) of 0.73-1.691/day [10,[15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%